Novel ICT Applications for Pacific Agri-Food and Nutritious Systems: Best Practices, Gaps and Opportunities in Fiji - Sharma, Bibhya; Izzal Azid, Sheikh; Nath, Reginald; Kumar, Krishneel; Sharma, Vikrant (Technical Centre for Agricultural and Rural Cooperation, 2018)
A study was conducted by a team led by Dr Bibhya Sharma of The University of the South Pacific on ICT tools used by the agricultural sector in Fiji. The seminal aim of the assignment, commissioned under the CTA-led project on Promoting Nutritious Food Systems in the Pacific Islands, is not only to create awareness in the Pacific but also to help farmers and consumers leverage on current and new ICT tools, such as mobile apps, 3D printers and blockchain technology for best results.